PENGARUH LINGKUNGAN KERJA DAN INTERAKSI INTERPERSONAL TERHADAP KEPUASAN KERJA KARYAWAN PADA KANTOR PUSAT PERUM DAMRI JAKARTA - I Ketut R. Sudiarditha (Jurnal Ilmiah Econosains, 2013)
ABSTRACTThe purposes of the research are: (1) To know description for working environment, interpersonal interaction, and job satisfaction at Head Office of Perum Damri Jakarta. )2) Test empirically influence of working environment towards job satisfaction at Head Office of Perum Damri Jakarta. (3) Test empirically influence of interpersonal interaction towards job satisfaction at Head Office of Perum Damri Jakarta. (4) Test empirically influence of working environment and interpersonal interaction towards job satisfaction at Head Office of Perum Damri Jakarta. The method of this research was simple random sampling, that taken 80 employee at Technique Directorate, Operational Directorate Financial Division, Human Resource, and Administration while data collecting by using questionnaire and cultivated using SPSS 17.0. The result of t test for working environment is 2,745, and the signification is 0.008. This shows that there is an effect between working environment toward job satisfaction. The result of t test for interpersonal interaction was 2.391, and the signification is 0.000. This shows that there is an effect between working environment toward job satisfaction. The result of F test is 5.471, and the signification is 0.000. This shows that there is an effect between working environment and interpersonal interaction toward job satisfaction. The result of R2 is 0.313 or 31.3%.Keywords: working environment, interpersonal interaction, job satisfaction